Il diritto ebraico nell’emergenza sanitaria = Jewish law and health emergencies - Di Segni, Riccardo (Quaderni di diritto e politica ecclesiastica, 2021)
The short article highlights, in the first part, major problems that epidemics posed to Halachà through the centuries. The second part shows how modern posekim dealt with similar questions during the recent Covid-19 pandemic.